2019
DOI: 10.1002/acr.23740
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds in the Relationship of Quadriceps Strength With Functional Limitations in Women With Knee Osteoarthritis

Abstract: In persons with symptomatic knee OA, thresholds in the strength function relationship may help identify individuals, especially women, at the brink of disability insofar as strength and daily tasks. In those with low strength, small increments in strength may be associated with improvement in function and greater ease with common daily life, emphasizing the importance of preventing loss of strength. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The weakness of muscles adjacent to the painful joint(s) is a common feature of OA. Adequate muscle strength is required for many activities of daily living [215,216] and muscle weakness is a major factor contributing to OA related functional disability [217,218]. In the lower limb, muscles may also have a protective role, attenuating mechanical loading of the OA joint during gait and other activities [27,219].…”
Section: Promising Directions For Clinical Practicementioning
confidence: 99%
“…The weakness of muscles adjacent to the painful joint(s) is a common feature of OA. Adequate muscle strength is required for many activities of daily living [215,216] and muscle weakness is a major factor contributing to OA related functional disability [217,218]. In the lower limb, muscles may also have a protective role, attenuating mechanical loading of the OA joint during gait and other activities [27,219].…”
Section: Promising Directions For Clinical Practicementioning
confidence: 99%
“…Knee extensor strength tends to be greater in individuals without knee OA than with knee OA [8], younger adults have greater strength than older adults [8,66,88], and middle-aged adults with knee OA have similar strength to older adults without knee OA [8]. Knee flexor and extensor strength also tends to be greater in males than females [18,50,51,61,105,107]. Body weight is inversely correlated with knee extensor strength more frequently in females than males [29,115], and those who develop incident knee OA [115].…”
Section: Resultsmentioning
confidence: 99%
“…Functional measurements have been associated with knee strength measurement utilizing isokinetic dynamometers. Knee strength has been identified as inversely associated with functional ambulation measures including the Get Up and Go Test [13,46,102,124,126], Timed Up and Go Test [26,49], 6 minute Walk Test [49,134], 100-meter walk test [123,124], 20-meter walk test [18], gait speed [92,93,122], and walking time [67]. Difficulty rising from a chair has been associated with lower knee extensor strength in females [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for self-paced walk tests was limited. However, a study conducted by Bacon et al (37) showed that quadriceps strength and 20-meter self-paced walk test may have non-linear relation in adults with symptomatic knee OA.…”
Section: Reliabilitymentioning
confidence: 98%